Exposure–response analysis of venetoclax in combination with rituximab in patients with relapsed or refractory chronic lymphocytic leukemia: pooled results from a phase 1b study and the phase 3 MURANO study. Issue 1 (2nd January 2020) - Deng, Rong; Gibiansky, Leonid; Lu, Tong; Li, Xiaobin; Lu, Dan; Li, Chunze; Girish, Sandhya; Wang, Jue; Boyer, Michelle; Shankar, Noopur; Humphrey, Kathryn; Freise, Kevin J.; et al.
Abstract: Exposure–response relationships from a phase 1b (M13-365) and phase 3 (MURANO) study were investigated to assess benefit/risk of venetoclax 400 mg daily plus rituximab in relapsed/refractory (R/R) chronic lymphocytic leukemia (CLL). Dose intensities were summarized by tertiles of predicted venetoclax steady-state average concentrations based on nominal venetoclax dose ( C meanSS, nominal ) for tolerability; exposure–safety analyses used logistic regression. Exposure–progression-free survival (PFS) relationships were assessed using MURANO data, with C meanSS, nominal as a grouping factor. Covariates were demographics, geographic region, study, baseline disease characteristics, ECOG performance status, responsiveness to prior therapy, and chromosomal abnormalities. There was no significant effect of covariates on grade ≥3 neutropenia/infection or PFS, and no relationship between venetoclax exposure and these endpoints, or venetoclax or rituximab dose intensity. These results support the recommended venetoclax 400 mg daily dose in combination with rituximab in patients with R/R CLL or small lymphocytic leukemia.